Active magnetic radiation shielding system analysis and key technologies. (January 2015) - Washburn, S.A.; Blattnig, S.R.; Singleterry, R.C.; Westover, S.C.
Abstract: Many active magnetic shielding designs have been proposed in order to reduce the radiation exposure received by astronauts on long duration, deep space missions. While these designs are promising, they pose significant engineering challenges. This work presents a survey of the major systems required for such unconfined magnetic field design, allowing the identification of key technologies for future development. Basic mass calculations are developed for each system and are used to determine the resulting galactic cosmic radiation exposure for a generic solenoid design, using a range of magnetic field strength and thickness values, allowing some of the basic characteristics of such a design to be observed. This study focuses on a solenoid shaped, active magnetic shield design; however, many of the principles discussed are applicable regardless of the exact design configuration, particularly the key technologies cited.